Managerial aspects of operating performance groups in agriculture - Szabados, György (Acta Agraria Debreceniensis, 2008)
Although we often witness groups, teams operating on various fields of life, we have not learnt much about various types of groups and teams in the agricultural sector, little is know about operational rules, internal properties, even less the managerial aspects. The Department of Management of University of Debrecen has been conducting research in this field for many years. In the framework of the research program, I have surveyed the managerial approach to identify main and typical characteristics of performance groups.During my researches I was determined to find out more about internal rules, relations and characteristics.